UKURAN PERUSAHAAN, PERPUTARAN MODAL KERJA DAN PERTUMBUHAN PENJUALAN TERHADAP RETURN SAHAM MELALUI PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Waskita, Sabrina Auli; Arief, Mohammad Yahya; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2025)
Banking companies are the pillars of a country’s economy. Therefore, banking plays a vital role in driving the wheels of the Indonesian economy. This study aimed to determine the effect of Company Size, Working Capital Turnover, and Sales Growth on Stock Returns as profits obtained by companies, individuals, and institutions from the results of investment policies they carry out with profitability. This research was conducted at Conventional Banking Companies listed on the IDX for 2019-2022. The population of this study was all Conventional Banking Companies, with a total of 41 companies. The sampling technique used was the purposive sampling technique. Based on the predetermined criteria, there were ten companies as samples. The data were secondary, and the research analysis tool used multiple linear regression using purposive sampling. This study’s data analysis and hypothesis testing used the Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of hypothesis testing regarding the direct impact using Smart PLS 3.0 show that Company Size has a positive effect on Profitability Working Capital Turnover; Sales Growth has a significant negative effect on Profitability, Company Size, Working Capital Turnover; Sales Growth and Profitability have a negative but insignificant effect on Stock Return; Company Size has a positive but insignificant effect on Profitability through Stock Return; Working Capital Turnover has a positive but insignificant effect on Profitability through Stock Return, Sales Growth has a positive but insignificant effect on Profitability through Stock Return.